High-activity beta-Ca2SiO4 for cultural relic protection and preparation and application thereof
Highly active β-Ca2SiO4 is prepared by using boron-containing crystal form stabilizers with low water solubility and high-temperature solid-phase synthesis method, and air-flood grinding and crushing treatment, the existing problems of high soluble salt content, large hydration and exothermic heat, and poor anti-aging performance in long-term use of existing cultural relics protection materials, achieving more efficient stone cultural relics protection.
Patent Information
- Application Number
- CN202510108959.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-23
AI Technical Summary
In the long-term use of existing cultural relics protection materials, there are problems such as high soluble salt content, large hydration and heat release, and poor anti-aging performance, which is difficult to meet the long-term protection needs of stone cultural relics.
A boron-containing crystal form stabilizer with low water solubility was prepared by high-active β-Ca2SiO4 by high-temperature solid phase synthesis method, and was crushed by airflow to improve the activity and performance of the material.
It significantly reduces the soluble salt content of the material, improves its compressive strength and durability, and enhances the protection effect of stone cultural relics.
Smart Images

Figure CN119911918A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cultural relics protection materials, in particular to a high-activity β-Ca2SiO4 for cultural relics protection and the preparation and application thereof. Background Art
[0002] Brick, tile and stone cultural relics are cultural relics made from artificial silicate bricks and tiles and natural stones, such as building bricks, tiles (dang), picture bricks (stones), grotto temples, cliff sculptures, stone carvings, stone inscriptions, stone tablets, sutra pillars, stone tools, etc. They are of various types, themes and styles. There are a large number of such cultural relics and they are widely distributed. These brick, tile and stone cultural relics are closely related to the activities of humans at that time, and have important historical, scientific and artistic values. They are rare, scarce and non-renewable cultural relic resources.
[0003] Bricks, tiles, and stone cultural relics are often damaged by various diseases due to natural environment, forces, earthquakes, and human damage. Among them, fractures, defects, surface weathering, and other diseases seriously affect the safety of the cultural relics themselves, and thus have an irreversible impact on their value. Immovable stone cultural relics are also commonly damaged by water and salt. The presence of water can cause secondary diseases including rock structure damage, weathering, microorganisms, and plants. The treatment of these diseases usually requires measures such as crack grouting, surface sealing, bonding reinforcement, and penetration reinforcement. Sometimes, repairs are required for defective parts.
[0004] Materials used for bonding and reinforcing bricks, tiles and stone cultural relics usually include organic, inorganic and organic-inorganic composite materials.
[0005] Organic reinforcement materials have been used in the protection of stone cultural relics for more than 60 years. Due to their good adhesion and flexibility, as well as good tensile stress resistance, they have been widely used in the protection of brick and stone cultural relics. At present, commonly used organic reinforcement materials include epoxy resin, acrylic resin and silicone materials. Among them, epoxy resin is a widely used reinforcement material with the advantages of high bonding strength, low curing temperature, low curing shrinkage, corrosion resistance and convenient process. In the 1970s, it was used by cultural relics protection workers in the protection project of Yungang Grottoes and achieved good results (Li Zhiguo, Fifty Years of Scientific and Technological Protection Research of Yungang Grottoes [J]. Cultural Relics World, 2004 (5): 3-7). However, long-term studies have found that the effective life of organic reinforcement materials in the field often does not meet the requirements of cultural heritage protection. The byproducts and residues after failure may also damage the cultural relics and are difficult to remove. The contradiction between the hydrophilicity of the stone itself and the hydrophobicity of the organic protective film (Liu Qiang, Zhang Bingjian, Long Mei, Research on the side effects of chemical protection of the hydrophobicity of the surface of stone cultural relics [J]. Cultural Relics Protection and Archaeological Science, 2006, 18 (2): 1-6) also makes the surface layer of the stone susceptible to stress damage and salt crystallization damage (Baglioni P, Giorgi R. Soft and hard nanomaterials for restoration and conservation of cultural heritage [J]. Soft Matter, 2006, 2 (4): 293-303). Therefore, considering the long-term effect, it is difficult for organic materials to meet the requirements of stone cultural relics protection.
[0006] The composite or hybridization of inorganic and organic materials to address the deficiencies of each material has attracted widespread attention in the past few decades (Kickelbick G. Concepts for the incorporation of inorganic building blocks into organic polymers on a nanoscale [J]. Prog Polym Sci, 2003, 28 (1): 83-114).Many materials, such as silicone and its modified materials (Huang Y, Liu W, Zhou X. Silicone / silica nanocomposites as culture-stone protective materials[J]. J Appl Polym Sci, 2012, 125(SI): 282-291), acrylic acid and its modified materials (Sabatini V, CattòC, Silvestro GD, et al. Protective features, durability and biodegration study of acrylic and methacrylic fluorinated polymer coatings for marble protection[J],Prog Org Coat, 2018, 114(2018): 47-57), epoxy resin and its modified materials (Pocius AV. Adhesion and Adhesives Technology[M]. Hanser, 2012), fluorine-silicon composite materials (Licchelli M, Marzolla SJ, Poggi A, et al. Cross-linked fluorinated polyurethanes for the protection of stone surfaces from graffiti[J]. J Cult Herit, 2011, 12 (1): 34-43), nano-inorganic material modified composite materials (Tian SP, Liu SJ, Gao F, et al. Preparation and Assessment of Superhydrophobic Organic-Inorganic Hybrid Coatings for Conservation of Yungang Grottoes [J]. Materials Research Society Symposium Proceedings. 2011, 1319 http: / / journals.Cambridge.org / abstract-s1946427411007366) and other materials have been gradually introduced into the anti-weathering protection of sandstone cultural relics, providing more options and opportunities for cultural relics protection. However, the long-term impact of the presence of organic components on protective materials has not been well evaluated.
[0007] Inorganic reinforcement materials are the earliest materials used in stone protection. The reinforcement mechanism of inorganic reinforcement materials is to use the condensation of inorganic substances in the pores of bricks and stones or to react chemically with the cement in the stone to form new substances, which reduces the voids in the stone and improves the structural strength, thereby playing a certain role in reinforcing and protecting brick and stone cultural relics. The inorganic reinforcement materials used at home and abroad include natural hydraulic lime (Zhang B, Liu P, Qi N, et al. Regulation of oxidation degree for graphene oxide on hydration process and engineering properties of natural hydraulic lime pastes for grout strengthening of stone cultural relics [J]. Construction & Building Materials, 2023 (Dec. 1): 407), lime water, barium hydroxide and alkaline earth silicate (Han Dongmei, Guo Guangsheng, Shi Zhimin, et al. Application of chemical reinforcement materials in the protection of stone cultural relics [J]. Cultural Relics Protection and Archaeological Science, 1999 (2): 41-44). As early as the 1970s, the British used lime water to reinforce the sculptures of Wells Cathedrals (Marsh P. Breathing new life into statues of Wells [J]. New Scientist, 1977, 76 (1083): 754-756). The Institute of Cultural Relics Protection of Dunhuang Academy in my country has developed a new inorganic reinforcement material for the reinforcement of stone cultural relics and earthen sites - PS (high modulus potassium water glass) material (Li Zuixiong, Stability and Strength Problems of PS Reinforced Earthen and Stone Cultural Relics [J]. Dunhuang Research, 1996 (3): 96-111). The material is mainly composed of potassium silicate aqueous solution with a modulus of 3.8 to 4.0, a curing agent, a cross-linking agent and a diffusing agent. It penetrates into the interior of weathered sandstone and can undergo complex physical and chemical reactions with carbonates, clay minerals and other components in the sandstone to form a fibrous inorganic complex containing a Si-O skeleton, thereby improving the connection strength between the particles inside the sandstone. Inorganic materials are consistent with the main materials of bricks and stone cultural relics, and have good anti-aging properties, but their permeability and adhesion are poor. Reinforcement materials are mainly found on the surface of stone cultural relics, and are prone to form a hard shell on the surface, affecting the air permeability of the stone, which is a bottleneck restricting the application of such materials in the protection of stone cultural relics. In addition, silicate cement has also been widely used in cultural relic restoration.
[0008] Although ordinary Portland cement can provide higher bonding strength, its high soluble salt content can cause secondary damage to cultural relics. In addition, the high hydration heat of Portland cement may also cause damage to masonry cultural relics.
[0009] Here, the inventors analyzed the main components (C3S, C2S, C3A, C4AF) in ordinary Portland cement clinker and believed that β-Ca2SiO4 (C2S) has the advantages of low hydration heat, high stone body strength, and excellent durability. They innovatively proposed to use this material in the protection practice of masonry cultural relics, and have achieved excellent results.
[0010] However, Ca2SiO4 has α, α′ H , α′ L There are many crystal forms such as β, γ, etc. Among them, the γ type has no hydration activity. Avoiding the formation of γ-Ca2SiO4 is the key and difficulty in preparing this cementitious material. H , α′ L )Ca2SiO4 can exist stably at high temperature, and the preparation of β-Ca2SiO4 has become a hot spot for this type of cementitious materials.
[0011] At present, the preparation of β-Ca2SiO4 mainly includes sol-gel method and solid phase synthesis method. Among them, the sol-gel method has a lower synthesis temperature, smaller particle size and better uniformity, so its activity is higher, but its preparation process is relatively complicated, the raw materials are expensive, the organic solvents used contain certain toxicity, and the production process has greater safety hazards, resulting in its high production cost. This method is not economical for industrial large-scale production. A small amount of materials prepared by this method are mainly used in scientific research and biomedicine. In the high-temperature solid-phase synthesis process, it is generally necessary to use certain special processing techniques to avoid the formation of γ phase in the final product, such as using rapid cooling operations or adding crystal stabilizers during the synthesis process. Among them, adding crystal stabilizers and supplementing with rapid cooling is a reliable way to stably prepare β-Ca2SiO4. Existing studies have shown that the ions that stabilize β-Ca2SiO4 mainly include K + ,Na + ,Ba 2+ ,B 3+ ,Al 3+ ,Mn 4+ ,P 5+ and S 6+ et al. (G.-C. Lai, T. Nojiri, K. Nakano, Studies of the stability of β-Ca2SiO4 doped by minor ions, Cem. Concr. Res. 22 (1992) 743-754).
[0012] Among them B 3+ It is a very effective β-Ca2SiO4 crystal stabilizer. Borax and boric acid are introduced into B 3+ As a crystal stabilizer, it can also effectively reduce the calcination temperature, which has obvious advantages. However, as a cultural relic protection material, it has a low soluble salt content requirement, and the sodium ions contained in borax make this additive unusable. When boric acid is used as a crystal stabilizer, the volatilization of boric acid at high temperature sometimes causes it to lose its due effect or requires excessive addition to achieve the desired crystal stabilization effect. In addition, borax and boric acid are both substances that are easily soluble in water. When wet grinding is used to process raw material powder, there is a disadvantage that the components are easily segregated during drying, which increases the difficulty of later homogenization. Existing studies have shown that the hydration activity of β-Ca2SiO4 is generally low, which is manifested in the low initial strength of the prepared test block, and the development of strength requires a long process. Therefore, it is crucial to provide a technical solution that can solve the above-mentioned technical problems. Summary of the invention
[0013] In order to solve the above problems, the purpose of the present invention is to provide a highly active β-Ca2SiO4 for cultural relics protection and its preparation and application.
[0014] For the introduction of B by boric acid 3+ When used as a crystal stabilizer, there are serious problems such as high-temperature volatilization. The present invention, based on the traditional solid-phase synthesis process, proposes to use a new type of boron-containing crystal stabilizer to obtain high-activity β-Ca2SiO4 through high-temperature solid-phase synthesis, or to obtain high-activity β-Ca2SiO4 through airflow grinding after high-temperature solid-phase synthesis. The present invention selects a boron-containing crystal stabilizer with low water solubility. On the one hand, it effectively reduces the volatilization of boron during high-temperature solid-phase reaction; on the other hand, during wet processing, it effectively avoids the uneven phenomena such as crystallization and stratification after drying caused by the use of water-soluble crystal stabilizers such as boric acid and sodium borate. In addition, the calcium and calcium-silicon elements contained in the introduced boron-containing crystal stabilizer are essential components for the synthesis of β-Ca2SiO4, and the soluble salt content in the high-activity β-Ca2SiO4 prepared by the present invention is lower.
[0015] The purpose of the present invention can be achieved by the following technical solutions:
[0016] The first object of the present invention is to provide a highly active β-Ca2SiO4 for cultural relics protection, which is prepared by solid phase synthesis method using calcium carbonate, silicon dioxide and a boron-containing crystal stabilizer;
[0017] Wherein, the boron-containing crystal stabilizer is selected from one or more of boron-calcium compounds or calcium-boron-silicon compounds.
[0018] In one embodiment of the present invention, the boron-calcium compound is selected from calcium metaborate (CaB2O4·6H2O), calcium borate or calcium pyroborate (Ca2B6O 11 5H2O) or more;
[0019] The calcium-boron-silicon compound is selected from one or more of calcium borosilicate (BCaSiH5O7) and colemanite (CaBSiO4(OH)).
[0020] In one embodiment of the present invention, the calcium borate is one of binary diborate (CaO·B2O3·nH2O) with the general formula xCaO·yB2O3·nH2O, binary tetraborate (CaO·2B2O3·nH2O), tetrabasic hexaborate (2CaO·3B2O3·nH2O), binary hexaborate (CaO·3B2O3·nH2O) or a combination thereof.
[0021] The second object of the present invention is to provide a method for preparing high-activity β-Ca2SiO4 for cultural relics protection, wherein the high-activity β-Ca2SiO4 for cultural relics protection is selected from one of β-Ca2SiO4 that has not been pulverized by jet mill or β-Ca2SiO4 that has been pulverized by jet mill;
[0022] The preparation of highly active β-Ca2SiO4 for cultural relics protection specifically includes the following steps:
[0023] (S1) mixing calcium carbonate, silicon dioxide and a boron-containing crystal stabilizer and then ball-milling the mixture to obtain a raw material;
[0024] (S2) calcining the raw material of the batch prepared in step (S1), and rapidly cooling to obtain β-Ca2SiO4 that has not been jet-milled;
[0025] Alternatively, the raw material of the batch prepared in step (S1) is calcined, rapidly cooled, and then subjected to a jet mill pulverization treatment to obtain jet mill pulverized β-Ca2SiO4.
[0026] In one embodiment of the present invention, in step (S1), the number of calcium atoms in calcium carbonate is twice the number of silicon atoms in silicon dioxide; the number of boron atoms in the boron-containing crystal stabilizer is 1 to 10% of the number of silicon atoms in silicon dioxide (preferably, the number of boron atoms in the boron-containing crystal stabilizer is 2 to 6% of the number of silicon atoms in silicon dioxide);
[0027] In one embodiment of the present invention, in step (S1), the ball milling treatment is selected from dry ball milling or wet ball milling.
[0028] In one embodiment of the present invention, the dispersant is selected from one or more of gum arabic, gelatin or an organic polymer water reducer; wherein, the addition of the dispersant can effectively reduce the moisture content in the slurry and save the energy consumption required for drying the slurry; the organic material can be completely decomposed at high temperature without causing residual harmful ions.
[0029] In one embodiment of the present invention, during the dry ball milling process, the rotation speed is 300 to 350 r / min and the time is 40 to 60 min;
[0030] During the wet ball milling process, a dispersant is added, the amount of the dispersant added is 0.8% to 1.2% of the total mass of calcium carbonate, silicon dioxide and boron-containing crystal stabilizer, the rotation speed is 330 to 360 r / min, and the time is 20 to 28 hours; after the wet ball milling is completed, a drying and crushing process is performed.
[0031] In one embodiment of the present invention, when the ball milling is wet ball milling, the boron-containing crystal stabilizer is a boron-containing crystal stabilizer with low water solubility;
[0032] Preferably, the boron-containing crystal stabilizer is CaB2O4·2H2O;
[0033] Preferably, the boron-containing crystal stabilizer is Ca2B6O 11 5H2O;
[0034] Preferably, the boron-containing crystal stabilizer is calcium borate;
[0035] Preferably, the boron-containing crystal stabilizer is Ca2B6O 11 A combination of 5H2O, CaB2O4·2H2O and calcium borate;
[0036] Preferably, the boron-containing crystal stabilizer is a calcium-boron-silicon compound with low water solubility.
[0037] In one embodiment of the present invention, in step (S2), during the calcination process, the temperature is 800-1500° C. and the time is 1-24 hours.
[0038] In one embodiment of the present invention, during the calcination process, the calcination temperature and calcination time are determined based on the particle size of the selected raw materials, the fineness of the powder after the raw material processing, and the amount of the boron-containing crystal stabilizer, and are determined based on the properties of the resulting clinker.
[0039] In one embodiment of the present invention, in step (S2), during the jet mill pulverization process (the particles are pulverized and further activated by high-speed collision), the feed nozzle pressure is 0.3-0.4 MPa, and the pulverization nozzle pressure is 0.6 MPa;
[0040] The particle size D of β-Ca2SiO4 crushed by jet mill 90 Less than 20μm.
[0041] In one embodiment of the present invention, the particle size of high-activity β-Ca2SiO4 for cultural relics protection is determined by parameters such as the working pressure and feeding speed of the air flow mill; it can be adjusted according to actual needs.
[0042] Preferably, the particle size D of the highly active β-Ca2SiO4 used for cultural relics protection is 90 Less than 15 μm;
[0043] Further preferably, the particle size D of the highly active β-Ca2SiO4 used for cultural relics protection is 90 Less than 10μm.
[0044] The third object of the present invention is to provide a method for preparing cultural relics protection products using highly active β-Ca2SiO4.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The present invention selects a boron-calcium compound, a calcium-boron-silicon compound or a combination thereof with low water solubility, thereby effectively reducing boron volatilization during high-temperature solid-phase reaction; during wet processing, the present invention effectively avoids uneven crystallization and stratification after drying caused by the use of water-soluble crystal stabilizers such as boric acid and sodium borate.
[0047] (2) The calcium and calcium-silicon elements contained in the boron-containing crystal stabilizer introduced by the present invention are essential components for the synthesis of β-Ca2SiO4. The high-activity β-Ca2SiO4 prepared by the present invention has a lower soluble salt content and a better doping effect of the crystal stabilizer. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 This is the X-ray diffraction pattern of the clinker prepared in Example 1 without being pulverized by jet mill.
[0049] Figure 2 The clinker prepared in Example 1 without being pulverized by jet mill ( Figure 2 (a)) and jet milled clinker ( Figure 2 (b)) Particle size distribution diagram.
[0050] Figure 3 The compressive strength of the clinker crushed by the air flow mill prepared in Example 1 at different ages.
[0051] Figure 4 This is a comparison chart of the compressive strength of the clinker prepared in Example 1 without being crushed by a jet mill and the clinker crushed by a jet mill.
[0052] Figure 5 This is the X-ray diffraction pattern of the clinker prepared in Comparative Example 1 without being pulverized by jet mill.
[0053] Figure 6 It shows the original state of the surface cracks of the North Hill of Dazu Rock Carvings and the apparent morphology of the clinker (β-Ca2SiO4) crushed by the air flow mill prepared in Example 1 after the plugging treatment. DETAILED DESCRIPTION
[0054] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0055] In the following examples, calcium carbonate (AR) and silicon dioxide (AR) were purchased from Sinopharm Chemical Reagent Co., Ltd., calcium borohydrite was obtained from Tieshan iron ore deposit in Daye, Hubei Province, and is a relatively pure natural calcium borohydrite (CaBSiO4(OH)); calcium borosilicate was purchased from Shanghai Hongtu Trading Co., Ltd. (BCaSiH5O7); calcium metaborate was purchased from Shaanxi Didu Pharmaceutical Chemical Co., Ltd.; calcium sclerobot was purchased from Wuhan Xingzhongcheng Technology Co., Ltd.; quaternary hexaborate was purchased from Chengdu Yuanmingxu Chemical Products Co., Ltd.; binary diborates, binary tetraborates and binary hexaborates were all purchased from Jinan Element Chemical Co., Ltd.
[0056] Unless otherwise specified, all reagents used are commercially available reagents, and all detection means and methods used are conventional detection means and methods in the art.
[0057] It should be noted that boron-calcium compounds and calcium-boron-silicon compounds have different trade names, and the water content represented in their expressions is sometimes not a fixed value. At the same time, these two types of artificial or synthetic compounds may have different compositions. However, a large number of experiments have found that these raw materials have similar effects when used as boron-containing crystal stabilizers.
[0058] Example 1: Colemanite as a boron-containing crystal stabilizer
[0059] This embodiment provides a method for preparing highly active β-Ca2SiO4 (β-Ca2SiO4 crushed by jet mill) for cultural relics protection, comprising the following steps:
[0060] (S1) 196 g of calcium carbonate, 57.6 g of silicon dioxide, and 6.4 g of colemanite (in this embodiment, the atomic ratio of boron atoms to silicon is 4%) are weighed and added into a 1 L ball mill, and 400 mL of water is added; after ball milling for 24 h, the mixture is dried at 105° C. for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0061] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0062] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.3 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0063] In this embodiment, the crystal structure of the clinker without jet milling and the clinker with jet milling was tested by X-ray diffractometer, and the particle size distribution of the powder was tested by laser particle size analyzer. Figure 1 As shown ( Figure 1 The results show that the synthesized clinker without jet milling is a pure β-Ca2SiO4 phase, that is, in this embodiment, the clinker without jet milling is β-Ca2SiO4 without jet milling, and the clinker with jet milling is β-Ca2SiO4 with jet milling; the particle size distribution of the clinker without jet milling and the clinker with jet milling is as follows: Figure 2 As shown in Figure 2, the particle size distribution of the clinker without jet milling is as follows: Figure 2 (a) as shown, D 90 =52.85μm; the particle size distribution of the clinker crushed by the jet mill is as follows Figure 2 (b) As shown in 90 =16.84μm.
[0064] The clinker without jet milling and the clinker with jet milling prepared in this example were mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold for curing at room temperature. After 24 hours, the samples were taken out of the mold and cured at 20±1℃ and 90±1% relative humidity for 1, 3, 7 and 28 days, respectively. The compressive strength of the samples of high-activity β-Ca2SiO4 powder at different ages is shown in Figure 2. Figure 3 As shown in the figure; the compressive strength comparison of clinker without air flow mill and clinker with air flow mill is as follows Figure 4 shown.
[0065] Example 2 Calcium borosilicate as a boron-containing crystal stabilizer
[0066] This embodiment provides a method for preparing highly active β-Ca2SiO4 for cultural relics protection, comprising the following steps:
[0067] (S1) 198 g of calcium carbonate, 58.8 g of silicon dioxide, and 3.92 g of calcium borosilicate (in this embodiment, the atomic ratio of boron atoms to silicon is 2%) are weighed and added to a 1 L ball mill, and 200 mL of water is added (1% of the mass of the raw material of the batch as a dispersant gelatin is added); after ball milling for 24 h, the mixture is placed at 105° C. and dried for 24 h, and then ground with an electric grinder for 2 h to obtain the raw material of the batch;
[0068] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0069] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.35 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0070] The X-ray diffraction pattern analysis showed that the prepared clinker without jet milling was pure β-Ca2SiO4. The D 90 =14.84μm.
[0071] The clinker prepared in this example without jet milling and the clinker with jet milling were uniformly mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold at room temperature for curing. After 24 hours, the sample was taken out of the mold and cured at 20±1°C and 90±1% relative humidity for 1, 3, 7 and 28 days, respectively. The compressive strength at each age was measured to be similar to that of Example 1.
[0072] Example 3 A mixture of colemanite and calcium borosilicate as a boron-containing crystal stabilizer
[0073] This embodiment provides a method for preparing highly active β-Ca2SiO4 for cultural relics protection, comprising the following steps:
[0074] (S1) 194 g of calcium carbonate, 52.8 g of silicon dioxide, 4.8 g of colemanite and 5.88 g of calcium borosilicate (in this embodiment, the atomic ratio of boron atoms to silicon is 6%) are weighed and added into a 1 L ball mill, and 400 mL of water is added; after ball milling for 24 h, the mixture is placed at 105° C. and dried for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0075] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0076] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the pulverization by the jet mill is 0.4 MPa, and the pressure of the pulverizing nozzle is 0.6 MPa.
[0077] According to the X-ray diffraction pattern analysis, the prepared clinker without being pulverized by air jet mill is pure β-Ca2SiO4, and the particle size of the clinker pulverized by air jet mill is similar to that of Example 1.
[0078] The clinker prepared in this example without jet milling and the clinker with jet milling were uniformly mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold at room temperature for curing. After 24 hours, the sample was taken out of the mold and cured at 20±1°C and 90±1% relative humidity for 1, 3, 7 and 28 days, respectively. The compressive strength at each age was measured to be similar to that of Example 1.
[0079] Example 4 Calcium metaborate as a boron-containing crystal stabilizer
[0080] This embodiment provides a method for preparing highly active β-Ca2SiO4 for cultural relics protection, comprising the following steps:
[0081] (S1) 197 g of calcium carbonate, 56.4 g of silicon dioxide, and 7.01 g of calcium metaborate (in this embodiment, the atomic ratio of boron atoms to silicon is 6%) are weighed and added to a 1 L ball mill, and 400 mL of water is added; after ball milling for 24 h, the mixture is placed at 105° C. and dried for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0082] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0083] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.3 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0084] According to the X-ray diffraction pattern analysis, the prepared clinker without being pulverized by air jet mill is pure β-Ca2SiO4, and the particle size of the clinker pulverized by air jet mill is similar to that of Example 1.
[0085] The clinker prepared in this example without jet milling and the clinker with jet milling were uniformly mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold at room temperature for curing. After 24 hours, the sample was taken out of the mold and cured at 20±1°C and 90±1% relative humidity for 1, 3, 7 and 28 days, respectively. The compressive strength at each age was measured to be similar to that of Example 1.
[0086] Example 5 Calcium borate as a boron-containing crystal stabilizer
[0087] This embodiment provides a method for preparing highly active β-Ca2SiO4 for cultural relics protection, comprising the following steps:
[0088] (S1) 197 g of calcium carbonate, 56.4 g of silicon dioxide, and 4.11 g of calcium borate (in this embodiment, the atomic ratio of boron atoms to silicon is 6%) are weighed and added to a 1 L ball mill, and 400 mL of water is added; after ball milling for 24 h, the mixture is dried at 105° C. for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0089] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0090] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the pulverization by the jet mill is 0.4 MPa, and the pressure of the pulverizing nozzle is 0.6 MPa.
[0091] According to the X-ray diffraction pattern analysis, the prepared clinker without being pulverized by air jet mill is pure β-Ca2SiO4, and the particle size of the clinker pulverized by air jet mill is similar to that of Example 1.
[0092] The clinker prepared in this example without jet milling and the clinker with jet milling were uniformly mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold at room temperature for curing. After 24 hours, the sample was taken out of the mold and cured at 20±1°C and 90±1% relative humidity for 1, 3, 7 and 28 days, respectively. The compressive strength at each age was measured to be similar to that of Example 1.
[0093] Example 6 A mixture of calcium metaborate and calcium borate as a boron-containing crystal stabilizer
[0094] This embodiment provides a method for preparing highly active β-Ca2SiO4 for cultural relics protection, comprising the following steps:
[0095] (S1) 197 g of calcium carbonate, 55.2 g of silicon dioxide, 2.34 g of calcium metaborate and 4.11 g of calcium borate (in this embodiment, the atomic ratio of boron atoms to silicon is 8%) are weighed and added to a 1 L ball mill, and 400 mL of water is added; after ball milling for 24 h, the mixture is dried at 105° C. for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0096] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0097] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.35 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0098] According to the X-ray diffraction pattern analysis, the prepared clinker without being pulverized by air jet mill is pure β-Ca2SiO4, and the particle size of the clinker pulverized by air jet mill is similar to that of Example 1.
[0099] The clinker prepared in this example without jet milling and the clinker with jet milling were uniformly mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold at room temperature for curing. After 24 hours, the sample was taken out of the mold and cured at 20±1°C and 90±1% relative humidity for 1, 3, 7 and 28 days, respectively. The compressive strength at each age was measured to be similar to that of Example 1.
[0100] Example 7: Tetrabasic Hexaborate as Boron-Containing Crystal Stabilizer
[0101] This embodiment provides a method for preparing highly active β-Ca2SiO4 for cultural relics protection, comprising the following steps:
[0102] (S1) 198 g of calcium carbonate, 56.4 g of silicon dioxide, and 4.29 g of tetrabasic hexaborate (in this embodiment, the atomic ratio of boron atoms to silicon is 6%) are weighed and added to a 1 L ball mill, and 400 mL of water is added; after ball milling for 24 h, the mixture is placed at 105° C. and dried for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0103] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0104] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.3 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0105] According to the X-ray diffraction pattern analysis, the prepared clinker without being pulverized by air jet mill is pure β-Ca2SiO4, and the particle size of the clinker pulverized by air jet mill is similar to that of Example 1.
[0106] The clinker prepared in this example without jet milling and the clinker with jet milling were uniformly mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold at room temperature for curing. After 24 hours, the sample was taken out of the mold and cured at 20±1°C and 90±1% relative humidity for 1, 3, 7 and 28 days, respectively. The compressive strength at each age was measured to be similar to that of Example 1.
[0107] Example 8 A mixture of a binary diborate and a binary tetraborate as a boron-containing crystal stabilizer
[0108] This embodiment provides a method for preparing highly active β-Ca2SiO4 for cultural relics protection, comprising the following steps:
[0109] (S1) 198.5 g of calcium carbonate, 57 g of silicon dioxide, 0.9 g of dibasic diborate and 2.49 g of dibasic tetraborate (in this embodiment, the atomic ratio of boron atoms to silicon is 5%) are weighed and added into a 1 L ball mill, and 400 mL of water is added; after ball milling for 24 h, the mixture is placed at 105° C. and dried for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0110] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0111] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.35 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0112] According to the X-ray diffraction pattern analysis, the prepared clinker without being pulverized by air jet mill is pure β-Ca2SiO4, and the particle size of the clinker pulverized by air jet mill is similar to that of Example 1.
[0113] The clinker prepared in this example without jet milling and the clinker with jet milling were uniformly mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold at room temperature for curing. After 24 hours, the sample was taken out of the mold and cured at 20±1°C and 90±1% relative humidity for 1, 3, 7 and 28 days, respectively. The compressive strength at each age was measured to be similar to that of Example 1.
[0114] Example 9 A mixture of colemanite, calcium metaborate and dibasic hexaborate as a boron-containing crystal stabilizer This example provides a method for preparing highly active β-Ca2SiO4 for cultural relics protection, comprising the following steps:
[0115] (S1) 195.5 g of calcium carbonate, 54.6 g of silicon dioxide, 3.2 g of colemanite, 2.34 g of calcium metaborate and 1.60 g of dibasic hexaborate (in this embodiment, the atomic ratio of boron atoms to silicon is 7%) were weighed and added to a 1 L ball mill, and 400 mL of water was added; after ball milling for 24 h, the mixture was placed at 105° C. and dried for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0116] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0117] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.3 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0118] According to the X-ray diffraction pattern analysis, the prepared clinker without being pulverized by air jet mill is pure β-Ca2SiO4, and the particle size of the clinker pulverized by air jet mill is similar to that of Example 1.
[0119] The clinker prepared in this example without jet milling and the clinker with jet milling were uniformly mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold at room temperature for curing. After 24 hours, the sample was taken out of the mold and cured at 20±1°C and 90±1% relative humidity for 1, 3, 7 and 28 days, respectively. The compressive strength at each age was measured to be similar to that of Example 1.
[0120] Example 10 A mixture of calcium borosilicate, calcium borate, dibasic diborate and dibasic hexaborate as a boron-containing crystal stabilizer
[0121] This embodiment provides a method for preparing highly active β-Ca2SiO4 for cultural relics protection, comprising the following steps:
[0122] (S1) 196.5 g of calcium carbonate, 54.0 g of silicon dioxide, 1.96 g of calcium borosilicate, 2.06 g of calcium borosilicate, 1.80 g of dibasic diborate and 1.6 g of dibasic hexaborate (in this embodiment, the atomic ratio of boron atoms to silicon is 9%) are weighed and added into a 1 L ball mill, and 400 mL of water is added; after ball milling for 24 h, the mixture is placed at 105° C. and dried for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0123] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0124] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the pulverization by the jet mill is 0.4 MPa, and the pressure of the pulverizing nozzle is 0.6 MPa.
[0125] According to the X-ray diffraction pattern analysis, the prepared clinker without being pulverized by air jet mill is pure β-Ca2SiO4, and the particle size of the clinker pulverized by air jet mill is similar to that of Example 1.
[0126] The clinker prepared in this example without jet milling and the clinker with jet milling were uniformly mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold at room temperature for curing. After 24 hours, the sample was taken out of the mold and cured at 20±1°C and 90±1% relative humidity for 1, 3, 7 and 28 days, respectively. The compressive strength at each age was measured to be similar to that of Example 1.
[0127] Comparative Example 1 Boric acid as a crystal stabilizer
[0128] (S1) 196 g of calcium carbonate, 57.6 g of silicon dioxide, and boric acid (in this comparative example, the atomic ratio of boron atoms to silicon is 4%) are weighed and added into a 1 L ball mill, and 400 mL of water is added; after ball milling for 24 h, the mixture is dried at 105° C. for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0129] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0130] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.3 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0131] The X-ray diffraction pattern of the prepared clinker without jet milling is as follows: Figure 5 The results show that the synthesized clinker without jet milling is almost entirely γ-Ca2SiO4 phase ( Figure 5 The "γ-C2S" in the graph represents the γ-Ca2SiO4 phase. This is because boric acid volatilizes severely at high temperatures and does not play the role of a crystal stabilizer. The test field made of the prepared clinker pulverized by jet milling cannot be solidified in the natural environment for 28 days, indicating that γ-Ca2SiO4 has no hydration activity.
[0132] Comparative Example 2: Colemanite as a boron-containing crystal stabilizer
[0133] (S1) 196 g of calcium carbonate, 57.6 g of silicon dioxide, and 6.4 g of colemanite (in this comparative example, the atomic ratio of boron atoms to silicon is 4%) were weighed and added to a 1 L ball mill, and 400 mL of water was added; after ball milling for 24 h, the mixture was dried at 105° C. for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0134] (S2) placing the raw material of the batch prepared in step (S1) into a corundum crucible, heating the mixture from room temperature to 1450° C. within 5 hours, then keeping the temperature for 4 hours, and cooling the mixture along with the furnace temperature to obtain a clinker that has not been pulverized by jet milling;
[0135] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.3 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0136] The X-ray diffraction pattern analysis showed that the prepared clinker without jet milling was pure β-Ca2SiO4.
[0137] The jet milled clinker prepared in this comparative example was uniformly mixed with deionized water at a water-cement ratio (w / c) of 0.4 to obtain a slurry; the obtained slurry was injected into a 4cm*4cm*4cm mold at room temperature for curing. After 24 hours, the sample was taken out of the mold and cured at 20±1°C and 90±1% relative humidity for 3, 7 and 28 days, respectively. The results are shown in Table 1.
[0138] Comparative Example 3: No Boron-containing Crystal Stabilizer
[0139] (S1) 196 g of calcium carbonate and 58.8 g of silicon dioxide were weighed and added to a 1 L ball mill, and 400 mL of water was added; after ball milling for 24 h, the mixture was dried at 105° C. for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0140] (S2) putting the raw material of the batch prepared in step (S1) into a corundum crucible, heating it from room temperature to 1450° C. within 5 hours, and then keeping it at that temperature for 4 hours, taking it out and cooling it rapidly with an electric fan, and obtaining a clinker that has not been pulverized by jet mill after cooling;
[0141] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.3 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0142] The X-ray diffraction pattern of the prepared clinker without jet milling shows that the synthesized clinker without jet milling is almost entirely γ-Ca2SiO4 phase. The test field made of slurry prepared by jet milling clinker cannot be solidified in natural environment for 28 days, indicating that γ-Ca2SiO4 has no hydration activity.
[0143] Comparative Example 4: No Boron-containing Crystal Stabilizer
[0144] (S1) 196 g of calcium carbonate and 58.8 g of silicon dioxide were weighed and added to a 1 L ball mill, and 400 mL of water was added; after ball milling for 24 h, the mixture was dried at 105° C. for 24 h, and then ground with an electric grinder for 2 h to obtain a raw batch;
[0145] (S2) placing the raw material of the batch prepared in step (S1) into a corundum crucible, heating the mixture from room temperature to 1450° C. within 5 hours, then keeping the temperature for 4 hours, and cooling the mixture along with the furnace temperature to obtain a clinker that has not been pulverized by a jet mill;
[0146] (S3) The clinker prepared in step (S2) that has not been pulverized by a jet mill is pulverized by a jet mill to obtain clinker pulverized by a jet mill, wherein the pressure of the feeding nozzle during the jet mill pulverization is 0.3 MPa and the pressure of the pulverizing nozzle is 0.6 MPa.
[0147] The X-ray diffraction pattern of the prepared clinker without jet milling shows that the synthesized clinker without jet milling is almost entirely γ-Ca2SiO4 phase. The test field made of slurry prepared by jet milling clinker cannot be solidified in natural environment for 28 days, indicating that γ-Ca2SiO4 has no hydration activity.
[0148] The compressive strength of the clinker prepared by the air flow mill in Example 1, the clinker prepared by the air flow mill in Comparative Example 2 and the materials prepared in the existing literature were compared, as shown in Table 1. It can be found from Table 1 that the compressive strength of the clinker prepared by the air flow mill in Example 1 at each age is much higher than the values reported in the existing literature, indicating the superiority of the clinker prepared by the air flow mill in Example 1.
[0149] Table 1 Comparison of mechanical strength of various materials
[0150]
[0151]
[0152] Among them, the relevant literature mentioned in Table 1 is as follows:
[0153] Literature [1]: JTZhang, WSZhang, JYYe, XHRen, L.Liu, WGShen, Influence of alkaline carbonates on the hydration characteristics of β-C2S. Constr.Build.Mater.296 (2021).
[0154] Literature [2]: P.Koutník, A.Soukup, P.Bezucha, J.Kohout, Properties of mortars based on β-belite-metakaolinite-hydrated lime binder system, Constr.Build.Mater.253(2020).
[0155] Literature [3]: N.El Fami, H.Ez-zaki, A.Diouri, O.Sassi, A.Boukhari, Improvement of hydraulic and mechanical properties of dicalcium silicate by alkalineactivation, Constr.Build.Mater.247(2020)
[0156] Literature [4]: Luo K, Zhang W, Ye J, et al. Mechanism of interaction between hydration-carbonation of C2S [J]. Construction and Building Materials, 2024, 412: 134891.
[0157] Literature [5]: Zhang W, Zhang J, Ye J, et al. Hydration kinetics and microstructure development of normal and NaAlO2-activated Al-dopedβ-C2Spastes[J]. Journal of the American Ceramic Society, 2022, 105(3): 2221-2233.
[0158] Embodiment 11
[0159] This embodiment provides an application of highly active β-Ca2SiO4 (β-Ca2SiO4 prepared in Example 1 and crushed by jet mill) in cultural relics protection, and the application process is as follows:
[0160] (A1) After the β-Ca2SiO4 prepared in Example 1 and the 80-mesh sand were uniformly mixed in a mass ratio of 1:1, water and polycarboxylic acid high-efficiency water-reducing agent were added at a water-binder ratio of 0.4 (the mixed addition amount of water and polycarboxylic acid high-efficiency water-reducing agent was 0.3% of the mass of the β-Ca2SiO4 crushed by the air flow mill), and then the mixture was rapidly stirred for 5 minutes using an electric stirrer to obtain mortar.
[0161] (A2) V-shaped grooves are cut according to the actual direction of the cracks on the surface of the North Hill of Dazu Rock Carvings. The evenly mixed mortar is filled into the V-shaped grooves using small art scrapers, scrapers and other tools, and the filling density of the plugging material is ensured as much as possible. After the filling is completed, the part exceeding the cracks is trimmed and wiped to minimize the impact of the plugging material on the rock surface. Finally, the surface of the plugging material is covered with wet cloth strips, and water is sprayed twice a day during the 15 days of maintenance to ensure that the plugging material has good performance under the necessary high-humidity maintenance conditions.
[0162] pass Figure 6 It can be found that the sealing material after the sealing treatment has a good bonding effect with the rock body of the Dazu Rock Carvings, and no obvious cracks appear after 6 months, which proves that the β-Ca2SiO4 prepared by the present invention has a good effect in practical applications.
[0163] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the explanation of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A highly active β-Ca2SiO4 for cultural relics protection, characterized in that: It is prepared by solid phase synthesis method using calcium carbonate, silicon dioxide and a boron-containing crystal stabilizer; Wherein, the boron-containing crystal stabilizer is selected from one or more of boron-calcium compounds or calcium-boron-silicon compounds.
2. The highly active β-Ca2SiO4 for cultural relics protection according to claim 1, characterized in that: The boron-calcium compound is selected from one or more of calcium metaborate, calcium borate or calcium pyroborate; The calcium-boron-silicon compound is selected from one or more of calcium borosilicate and colemanite.
3. A method for preparing highly active β-Ca2SiO4 for cultural relics protection as claimed in any one of claims 1 to 2, characterized in that: The highly active β-Ca2SiO4 for cultural relics protection is selected from one of β-Ca2SiO4 that has not been ground by jet mill or β-Ca2SiO4 that has been ground by jet mill; The preparation of highly active β-Ca2SiO4 for cultural relics protection specifically includes the following steps: (S1) mixing calcium carbonate, silicon dioxide and a boron-containing crystal stabilizer and then ball-milling the mixture to obtain a raw material; (S2) calcining the raw material of the batch prepared in step (S1), and rapidly cooling to obtain β-Ca2SiO4 that has not been jet-milled; Alternatively, the raw material of the batch prepared in step (S1) is calcined, rapidly cooled, and then subjected to a jet mill pulverization treatment to obtain jet mill pulverized β-Ca2SiO4.
4. The method for preparing highly active β-Ca2SiO4 for cultural relics protection according to claim 3, characterized in that: In step (S1), the number of calcium atoms in calcium carbonate is twice the number of silicon atoms in silicon dioxide; the number of boron atoms in the boron-containing crystal stabilizer is 1 to 10% of the number of silicon atoms in silicon dioxide.
5. The method for preparing highly active β-Ca2SiO4 for cultural relics protection according to claim 3, characterized in that: In step (S1), the ball milling treatment is selected from dry ball milling or wet ball milling.
6. The method for preparing highly active β-Ca2SiO4 for cultural relics protection according to claim 5, characterized in that: During the dry ball milling process, the rotation speed is 300-350 r / min and the time is 40-60 min.
7. The method for preparing highly active β-Ca2SiO4 for cultural relics protection according to claim 5, characterized in that: During the wet ball milling process, a dispersant is added, the amount of the dispersant added is 0.8% to 1.2% of the total mass of calcium carbonate, silicon dioxide and boron-containing crystal stabilizer, the rotation speed is 330 to 360 r / min, and the time is 20 to 28 hours; after the wet ball milling is completed, a drying and crushing process is performed.
8. The method for preparing highly active β-Ca2SiO4 for cultural relics protection according to claim 3, characterized in that: In step (S2), during the calcination process, the temperature is 800 to 1500° C. and the time is 1 to 24 hours.
9. The method for preparing highly active β-Ca2SiO4 for cultural relics protection according to claim 3, characterized in that: In step (S2), during the jet mill pulverization process, the feed nozzle pressure is 0.3-0.4 MPa, and the pulverization nozzle pressure is 0.6 MPa; The particle size D of β-Ca2SiO4 crushed by jet mill 90 Less than 20μm.
10. Use of the highly active β-Ca2SiO4 for cultural relics protection as claimed in any one of claims 1 to 2 in the preparation of cultural relics protection products.
Citation Information
Patent Citations
Calcium borate silicate biological material, preparation method and application of calcium borate silicate biological material
CN104058730A
Stone cultural relic reinforcing and protecting material as well as preparation method and application thereof
CN114133208A
Boron-phosphorus composite modified high belite sulphoaluminate cement clinker and preparation method thereof
CN115710095A
Preparation and application of hydrated calcium silicate neat paste material and grouting material
CN116768593A
Preparation and application of hydrated calcium silicate neat paste material and grouting material
CN118930216A
Cited By
Preparation and application of modified beta-Ca2SiO4-based anti-weathering reinforcing material for surface layers of stone cultural relics
CN121317792A